When Empathy Matters: The Role of Sex and Empathy in Close Friendships. Issue 4 (13th May 2016) - Ciarrochi, Joseph; Parker, Philip D.; Sahdra, Baljinder K.; Kashdan, Todd B.; Kiuru, Noona; Conigrave, James
Abstract: Based on prior theory and research (Ciarrochi & Heaven, 2009; Eagly & Wood, 1999), we hypothesized that the link between empathy and friendship would be moderated by sex: Girls will nominate empathic boys as friends, whereas boys will not tend to nominate empathic girls. We collected measures of empathy, friendship social support, and close friendship nominations in grade 10 across 1, 970 students in 16 schools ( M age  = 15.70, SD  = .44; males = 993, females = 977). Multilevel models revealed that boys high in cognitive empathy attracted an average of 1.8 more girl friendship nominations than did their low empathy counterparts, whereas empathic girls did not attract a greater number of opposite‐sex friends. In addition, the more friendship nominations a boy received from either boys or girls, the more they felt supported by their friends; the number of friendship nominations received by girls, in contrast, had no effect on their felt support by friends. Regardless of the quantity of friendship nominations, empathy was linked to more supportive friendships for both males and females. These results inform a contextual understanding of the role of empathy in selecting and maintaining friendships.